Influence of cadmium and phosphorus enhance absorption and membrane damage in wheat seedlings grown in nutrient medium. (3rd April 2018) - Kumar, Ram; Gopal, Rajeev; Sharma, Y. K.
ABSTRACT: The effects of cadmium (Cd) and their amelioration with phosphorus (P) on plant growth, antioxidative components, and accumulation of Cd, iron (Fe), and zinc (Zn) were studied in wheat ( Triticum aestivum L.) seedlings. Reduced biomass and chlorophyll contents under the influence of Cd were observed to be increased on P application. As compared to control, the content of NP-SH, proline, and cysteine were observed to be increased in Cd treated seedlings which was also comparatively higher in Cd with P exposed seedlings. The activities of CAT, POX, SOD, APX, and GR were increased both in root and shoot at lower dose of Cd but reduced at higher dose, while P application enhanced the activity of these enzymes even at higher dose. Application of P, reduced the uptake of Cd but enhanced the accumulation of Fe and Zn both in root and shoot tissue. A close relationship existed between lipid peroxidation and tissue metal concentration.